Study of the genus Curcuma in Indonesia used as traditional herbal medicines - DYAH SUBOSITI; SLAMET WAHYONO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Subositi D, Wahyono S. 2019. Study of the genus Curcuma in Indonesia used as traditional herbal medicines. Biodiversitas 20: 1356-1361. Research into local knowledge is very important in providing a database of medicinal plants and as a basis for further research. The genus Curcuma (Zingiberaceae) has been used as medicines and other purposes, so it has a high economic value.  The aim of this study was to record the use of the species of the genus Curcuma as traditional herbal medicines in Indonesia. The study was a part of a project called RISTOJA (Research on Medicinal Plants and Traditional Herbal Medicines), which collected data from 415 ethnic groups in Indonesia from 2012 to 2017. A purposive sampling method was used to select 2,354 respondents (traditional healers) for interviews, 1,042 of whom used Curcuma as herbal medicines. It was found that eight species of the genus were used to treat 73 different ailments. Curcuma longa was found to have the highest relative frequency of citation (0.274) and use value (0.563), and members of the genus Curcuma were found to be extensively used to treat a wide variety of ailments in Indonesia.